PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA KARTU KUARTET TERHADAP KEMAMPUAN BEPIKIR KRITIS PESERTA DIDIK KELAS IV SDN GELAM I CANDI SIDOARJO - Siti Fatimah; Fakhrur Rozy (JIP: Jurnal Ilmu Pendidikan, 2025)
In the 21st century, students are required to have critical thinking skills to analyze problems. One example is SDN Gelam I Candi Sidoarjo, where students still lack critical thinking skills. The purpose of this study is to analyze the effect of the jigsaw cooperative learning model assisted by quartet cards on the critical thinking skills of fourth-grade students at SDN Gelam I Candi Sidoarjo. This study was conducted in a fourth-grade class with 20 students. The research design was quantitative pre-experimental with a one-group pre-test post-test design. The results of this study showed 0.118 > 0.054, which is normally distributed. The paired sample test showed 0.000 < 0.05, indicating a significant difference between the quartet card media and the jigsaw cooperative learning model.